2018
DOI: 10.1038/s12276-017-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the p53-SOCS2 axis contribute to tumor growth in colon cancer

Abstract: Altered expression of suppressor of cytokine signaling (SOCS) is found in various tumors. However, regulation of SOCS2 by upstream molecules has yet to be clearly elucidated, particularly in tumor cells. SCOCS2 expression was examined in tumor cells transfected with an inducible p53 expression system. The impact of SOCS2 on cell proliferation was measured with in vitro assays. Inhibition of tumorigenicity by SOCS2 knockdown was assessed via a mouse model. Expression profiles were compared and genes differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A study has demonstrated that SOCS2 was upregulated and then promote hippocampal neurogenesis and neuronal protrusive growth in vitro [20]. Meanwhile, the heterogeneously overexpression of SOCS2 was found in some colon cancers [21]. It has been suggested previously that miR-204-5p was low expressed in tumor tissues while high expressed in adjacent healthy tissues [22].…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that SOCS2 was upregulated and then promote hippocampal neurogenesis and neuronal protrusive growth in vitro [20]. Meanwhile, the heterogeneously overexpression of SOCS2 was found in some colon cancers [21]. It has been suggested previously that miR-204-5p was low expressed in tumor tissues while high expressed in adjacent healthy tissues [22].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a role of SOCS2 not only as a negative regulator of the JAK-STAT pathway, but also as a downstream target of it. Oncogenic roles of SOCS2 were also reported in other tumor entities: SOCS2 levels were elevated in colon and prostate cancer, and high SOCS2 expression was associated with a poor prognosis in the latter 23,24 . The transcription of SOCS2 was repressed by wild type p53, and it promoted proliferation, anchorage independent growth, resistance against basal and drug induced apoptosis, and tumor growth in xenograft assays in prostate and colon cancer cell lines 2325 .…”
Section: Discussionmentioning
confidence: 68%
“…Oncogenic roles of SOCS2 were also reported in other tumor entities: SOCS2 levels were elevated in colon and prostate cancer, and high SOCS2 expression was associated with a poor prognosis in the latter 23,24 . The transcription of SOCS2 was repressed by wild type p53, and it promoted proliferation, anchorage independent growth, resistance against basal and drug induced apoptosis, and tumor growth in xenograft assays in prostate and colon cancer cell lines 2325 . Because our data regarding Socs2 expression and growth regulatory effects of Socs2 derived from TP53 wt mice/cells and TP53 mutant human myeloid cells, we suggest that these effects are independent of p53 and TP53 mutations in AML.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, Das et al unveiled that low levels of SOCS2 was strongly linked to disease recurrence and metastasis in clinical specimens, and SOCS2 overexpression inhibited metastatic features of prostate cancer cells [ 39 ]. Conflicting data for SOCS2 were also observed in colorectal cancer (CRC) [ 40 , 41 ]. Differences between SOCS2 mRNA and protein levels might be attributed to the active degradation of SOCS2 protein [ 42 ].…”
Section: Discussionmentioning
confidence: 99%